Knowledge Management Maturity in Public Administration: A Case Study of a Higher Education Institution - Cristina Cotrim; Florinda Matos; Carolina Marques; Nuno Matos (European Conference on Knowledge Management, 2026)
Knowledge Management (KM) is increasingly recognised as a strategic capability for improving organisational learning, innovation and public service performance. In Public Administration (PA), where demands for efficiency, transparency and accountability are growing, assessing KM maturity can help institutions identify existing practices, diagnose barriers and define improvement actions. However, empirical evidence on KM maturity in Portuguese public organisations, particularly in public higher education institutions, remains limited. This paper examines how assessing KM maturity can enhance the effectiveness and efficiency of public service delivery. The study adopts a qualitative case study approach in a Portuguese public higher education institution. Data were collected through 30 semi-structured interviews with middle managers and quality management staff, complemented by documentary analysis of the institution’s Integrated Quality Management System (IQMS). The analysis was structured around the seven criteria of the Knowledge Management Assessment Instrument for Public Administration (IAGCAP): KM leadership, processes, people, technology, knowledge processes, learning and innovation, and KM results. Findings indicate that the institution has reached an overall KM maturity level 4, “refinement”, as several KM-related practices are implemented, monitored and improved. These include strategic planning mechanisms, quality management processes, institutional repositories, document management systems, internal manuals and collaborative digital tools. The results also reveal that KM is supported by an organisational culture that values learning, collaboration and continuous improvement. Nevertheless, relevant barriers remain, including limited interoperability between information systems, an outdated intranet, insufficient formal and informal knowledge-sharing spaces, weak institutional communication, and the absence of specific indicators to measure the impact of KM initiatives. The paper highlights that KM maturity assessment not only classifies an organisation’s KM level but also fosters its improvement. The case study demonstrates that the assessment enhances effectiveness by making KM practices visible, identifying barriers to knowledge flows, linking improvement opportunities to the IQMS, and emphasising KM-specific performance indicators. This study expands the use of KM maturity models in knowledge-intensive public organisations, illustrating their role in quality management, organisational learning, and innovation in public higher education.